Хүннү ба өмнөд, өрнөд хөршийн харилцаа холбоо - З.Батсайхан (Politology, 2023)
In this article we tried to define Xiongnu and Han dynasty, Xiongnu and Western countries political relations. The studies reveal that The Xiongnus’ relationship with the two neighboring countries mentioned above was based on entirely different approaches. The Xiongnu foreign policy regarding its 2 neighbors was to make them dependent states. Chinese Hans relations with Xiongnu and Western countries helped to shape Chinese foreign policy principles with northern nomads